Proof of concept: visual categorization of carotenoid pigmentation in Arctic charr (Salvelinus alpinus L) can predict stress response - Backstrom, Tobias; Brännäs, Eva; Nilsson, Jan; Carlberg, Hanna; Johansson, Kajsa; Magnhagen, Carin (2021)
Carotenoid pigmentation in Salvelinus alpinus has been connected to stress responsiveness in earlier studies. This has, however, only been tested with time-consuming image analysis from photos. Here, we used quick visual categorization of carotenoid pigmentation to investigate the stress responsiveness of the extreme groups. The visually selected charr were then exposed to a net restraint stressor. Arctic charr with few spots also had a lower stress responsiveness compared to charr with many spots. Thus, visual selection could be used as a simple method within aquaculture.